2022
DOI: 10.3390/s22134782
|View full text |Cite
|
Sign up to set email alerts
|

Battery-Free Wireless Light-Sensing Tag Based on a Long-Range Dual-Port Dual-Polarized RFID Platform

Abstract: Radio frequency identification (RFID) represents an emerging platform for passive RF-powered wireless sensing. Differential Multi-port RFID systems are widely used to enable multiple independent measurands to be gathered, or to overcome channel variations. This paper presents a dual-port/dual-integrated circuit (IC) RFID sensing tag based on a shared aperture dual-polarized microstrip antenna. The tag can be loaded with different sensors where the received signal strength indicator (RSSI) of one IC is modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…dielectric changes due to soil moisture variation or ice accumulation 21 , 22 , or vital signs using wearable antennas 23 . Moreover, RF sensor readout has been widely used based on additional functional sensors including 2D materials 24 , conductive polymers 25 , 26 , inorganic sensitive materials 27 , lumped sensors 28 , and even bacterial cultures 29 . For gas sensing, it was shown that reading the response of resistive sensors at kHz frequencies can improve their linearity and sensitivity 30 .…”
Section: Introductionmentioning
confidence: 99%
“…dielectric changes due to soil moisture variation or ice accumulation 21 , 22 , or vital signs using wearable antennas 23 . Moreover, RF sensor readout has been widely used based on additional functional sensors including 2D materials 24 , conductive polymers 25 , 26 , inorganic sensitive materials 27 , lumped sensors 28 , and even bacterial cultures 29 . For gas sensing, it was shown that reading the response of resistive sensors at kHz frequencies can improve their linearity and sensitivity 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Changes were made to this version by the publisher prior to publication. The final version of record is available at http://dx.doi.org/10.1109/JRFID.2023.3268422 body phenomena, including variations of temperature [12], humidity [22], pressure [23] and light [24]. Table I reports examples of the most assessed sensing helpful for PoCs that can be categorized into three types: i) physical, ii) behavioural, and iii) chemical.…”
Section: Introductionmentioning
confidence: 99%
“…RFID sensing has the advantage of relying on a single low-cost RFID IC for providing the unique ID of the backscattered RF signal that is amplitude-modulated by the measurand. RFID sensing has been incorporated in various applications ranging from vital signs monitoring using textile antennas [2], supply chain security [3], [4], wireless ice detection [5], as well as loaded by sensors for on-body temperature sensing [6] or indoor light intensity monitoring [7].…”
Section: Introductionmentioning
confidence: 99%